2010
DOI: 10.1161/hypertensionaha.110.150722
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease in Persons With Undiagnosed or Prehypertension in the United States

Abstract: Abstract-Hypertension is both a cause and a consequence of chronic kidney disease, but the prevalence of chronic kidney disease throughout the diagnostic spectrum of blood pressure has not been established. We determined the prevalence of chronic kidney disease within blood pressure categories in 17 794 adults surveyed by the National Health and Nutrition Examination Survey during 1999 -2006. Diagnosed hypertension was defined as self-reported provider diagnosis (nϭ5832); undiagnosed hypertension was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 18 publications
7
75
1
4
Order By: Relevance
“…So, the prevalence of CKD is higher in hypertensive than diabetic subjects. Result of this study is comparable with the study of Timothy HM et al who has also shown that in his 402 high risk subjects with hypertension, diabetes, 20.4% had CKD, and higher prevalence among hypertensive than diabetic (69% and 30% respectively) 16 Deidra C et al 17 have determined the prevalence of CKD within blood pressure categories in 17,794 adults. Prevalence of CKD among those with pre-and undiagnosed hypertension was 17.3% and 22.0%, respectively, compared to 27.5% with diagnosed hypertension Hida M et al 18 has studied Age distribution at dialysis induction among patients with CKD in 579 cases.…”
Section: Discussionsupporting
confidence: 88%
“…So, the prevalence of CKD is higher in hypertensive than diabetic subjects. Result of this study is comparable with the study of Timothy HM et al who has also shown that in his 402 high risk subjects with hypertension, diabetes, 20.4% had CKD, and higher prevalence among hypertensive than diabetic (69% and 30% respectively) 16 Deidra C et al 17 have determined the prevalence of CKD within blood pressure categories in 17,794 adults. Prevalence of CKD among those with pre-and undiagnosed hypertension was 17.3% and 22.0%, respectively, compared to 27.5% with diagnosed hypertension Hida M et al 18 has studied Age distribution at dialysis induction among patients with CKD in 579 cases.…”
Section: Discussionsupporting
confidence: 88%
“…Prevalence of CKD among the 17,794 adults surveyed in the U.S. NHANES 1999-2006 with prehypertension and undiagnosed hypertension were 17.3% and 22.0%, respectively, compared with 27.5% with diagnosed hypertension and 13.4% with normal blood pressure (Crews et al 2010). Table 1 provides a summary of epidemiologic studies showing Cd exposure as a risk factor in CKD, and two common disorders (diabetes and hypertension) that are closely linked with CKD development and progression to ESKD (Islam et al 2009).…”
Section: Cadmium -Chronic Kidney Diseasementioning
confidence: 97%
“…1 There is a significantly higher prevalence in the elderly and those with hypertension or diabetes, and with these comorbidities increasing in prevalence and the population ageing, CKD is projected to affect up to 16% of adults by 2030. 2,3 Even in its early stages, CKD is associated with accelerated cardiovascular disease and increased mortality, with an exponential increase in attributable risk as GFR declines to end-stage kidney disease (ESKD). 4,5 The mortality rate in ESKD patients maintained on dialysis is striking, with a life expectancy less than one-third that of their counterparts without ESKD, and a 5-year survival rate on dialysis of only 40%.…”
Section: Introductionmentioning
confidence: 99%